A sophisticated fracture classification system of the proximal femur trochanteric region (AO/OTA-31A) based on 3D-CT images - Chang, Shi-Min; Wang, Zhen-Hai; Tian, Ke-Wei; Sun, Gui-Xin; Wang, Xin; Rui, Yun-Feng (Frontiers in Surgery, 2022)
Objective: Fracture classification evolves dynamically with new and enhanced imaging modalities. The aim of this paper is to introduce a novel hypothesis of sophisticated fracture classification system for the proximal femur trochanteric region (AO/OTA-31A) based on 3D-CT images, and accommodate to the clinical requirement of the world-wide outbreak of geriatric hip fractures with large amounts of surgical operations. Methods: In the current practice of widely preoperative 3D-CT application and cephalomedullary nailing, we attempt to propose a new comprehensive classification system to describe the fracture characteristics in a more detailed and sophisticated architecture, and pay the most important concern to the parameters that contributing to fracture stability reconstruction in osteosynthesis. Results: The new four-by-four comprehensive classification system, followed the structure of AO/OTA system, incorporates many fracture characteristics as dividing indexes in multiple grade levels, including fracture line direction, number of fragments, the lesser trochanter fragment and its distal extension (>2cm), the posterior coronal fragment and its anterior expansion (to the entry portal of head-neck implant at the lateral cortex), lateral wall and anterior cortex fracture, and the anteromedial inferior corner comminution. From a panoramic perspective, there are four types and each type has four subtypes. A1 is simple two-part fractures (20%), A2 is characterized by lesser trochanter fragment and posterior coronal fractures (62.5%), A3 is reverse obliquity and transverse fractures with complete lateral wall broken (15.5%), and A4 is medial wall comminution which further lacks anteromedial cortex transmission of compression force (2%). For subtypes, A2.2 is with a banana-like posterior coronal fragment, A2.4 is with distal cortex extension >2cm of the lesser trochanter and anterior expansion of the posterior coronal fragment(s) to the entry portal of head-neck implants, A3.4 is a primary pantrochanteric fracture, and A4.4 is a concomitant ipsilateral segmental fracture of the neck and trochanter region. Conclusion: Classification represents diversity under consistency. The four-by-four sophisticated classification system delineates fracture characteristics in more detail. It is applicable in the time of rapid outbreak of trochanteric fractures in older population, the large amounts of surgical operations, and incorporates various rare and/or more complicated subtypes which is nonclassifiable before.